Lobomycosis-like disease epidemiology, pathology and social affiliations in bottlenose dolphins from Southwestern Gulf of Mexico - Gálvez, Casandra; Tenorio-Osorio, Mónica; Hernández-Candelario, Isabel; Delfín-Alfonso, Christian Alejandro; Morteo, Eduardo (Frontiers in Marine Science, 2022)
Mycotic diseases are considered a worldwide growing concern related to public health. Lobomycosis like disease (LLD) (Lacazia loboi) is a chronic and progressive infection in skin of humans and small cetaceans present in both sides of the Americas, including Mexico but information is still limited. Marine predators are indicators of potential risks for human and wildlife health, including fungal diseases like LLD in bottlenose dolphins. Here we report the first findings of an initial assessment in LLD epidemiology, pathology, and behavioral constraints of coastal bottlenose dolphins (Tursiops truncatus) from the Southwestern Gulf of Mexico (SWGM). Overall, LLD prevalence in the population was low, within ranges reported for the species, and only in highly associated unisexual pairs near the Alvarado coastal waters. Photo-identified individuals exhibited an annual increase in average progression for LLD skin lesions. Gross lesions and skin biopsy evidenced mycotic structures and subcutaneous alterations associated to LLD. Habitat quality, demographic, and social characteristics of bottlenose dolphins are likely influencing LLD geographical expansion and temporal prevalence, but global and local climate variability may influence LLD epidemiology, implying a potential risk for human and dolphin health from coastal communities at the SWGM.